Zen ghosts - Muth, Jon J. (New York : Scholastic Press, 2010)
On Halloween night, Stillwater the giant panda tells Karl, Addy, and Michael a spooky and unusual story. Based on a Zen koan.
Pub Weekly, August 2010
2.8
K-3
Keywords: Giant panda -- Juvenile fiction; Pandas -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Storytelling -- Juvenile fiction; Halloween -- Juvenile fiction; Giant panda -- Fiction; Pandas -- Fiction; Brothers and sisters -- Fiction; Storytelling -- Fiction; Halloween -- Fiction; Giant pandas -- Fiction; Pandas -- Fiction; Siblings -- Fiction; Storytelling -- Fiction; Halloween -- Fiction; Picture books for children